Pengaruh Dosis Ovaprim Terhadap Indeks Kematangan Gonad Ikan Komet Carassius auratus - Tamar Mustari (AquaMarine (Jurnal FPIK UNIDAYAN ), 2021)
In the world of ornamental fish business, Indonesian products are known to have many species of freshwater ornamental fish, one of which is the goldfish Carassius auratus. In aquaculture activities, hatchery techniques that are still minimally mastered by fish cultivators are the main problem in these activities. Artificial hatchery techniques for fish can use the ovaprim hormone as a material in accelerating the gonadal maturity level in fish. This study aims to determine the appropriate dose of ovaprim hormone for gonadal maturity index and spawning latency time after injecting ovaprim hormone at different doses to goldfish (Carassius auratus). The study was conducted for 28 days, using aquarium media with a capacity of 40 liters, as many as 12 pieces and filled with fresh water that had been sterilized. The main ingredient of the hormone ovaprim Syndel uk. 10 ml and 100 ml of 0.9% NaCl as a hormone solvent. The organisms used were goldfish Carassius auratus with Gonad Maturity Level I, as many as 3 individuals with a male to female ratio of 1:2. The design used was a completely randomized design, 4 treatments and 3 replications namely A (0.2 ml/kg ovaprim), 0.4 ml/kg B (0.4 ml/kg ovaprim), C (0.6 ml/kg ovaprim), and D (ovaprim 0.8 ml/kg). The results showed that the best goldfish (Carassius auratus) gonadal maturity index was found in C treatment (0.6 ml/kg ovaprim), namely 6.11+0.08%, and the lowest in D treatment (0.8 ml/kg ovaprim, namely 5.61+0.05%. The fastest spawning latency occurred in C treatment (0.6 ml/kg ovaprim), which was 9 hours 46 minutes and the longest was found in A treatment (0.2 ml/kg ovaprim) which was 12 hours 22 minutes.